An achievement test in English for grade one Waray learners - Ignacio, Gregoria Pedere 1923- (s.n.], 1971)
This is an achievement test in English in a second language situation. This test has been designed specifically for Grade I Waray learners of English of Burauen III Central School, Burauen Leyte and other Waray-speaking children. This study attempts to measure grade one pupils' knowledge and understanding, abilities and skills in the three elements of English namely: phonology, grammar and vocabulary. Likewise, it seeks to measure Grade I pupils' progress and to gain insights to some of the problems of English instruction in the lower grades, particularly in grade one. Statistical analysis revealed that this test is both valid and highly reliable.